Interactive Quiz-Based Flashcards for Islamic Religious Education: A Development Study at the Junior High School Level - Fatimah Az Zahrah; Siti Rohimah; Meti Fatimah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to develop interactive quiz-based flashcard learning media to support Islamic Religious Education (ISE) learning at the junior high school level. The research method employed was Research and Development (RD) using the ADDIE model, which encompasses analysis, design, development, implementation, and evaluation. The results of the needs analysis indicated that students require simple, engaging media that motivates them to be more active. The flashcard product was designed with two sides (questions and answers) and equipped with illustrations and a QR code that connects students to an online quiz. Validation by material experts, media experts, and practitioners showed a